Importance of jackals and domestic dogs for the transmission of generalist canid pathogens to sympatric carnivores in Namibia - Gowtage-Sequeira, Sonya (The University of Edinburgh, 2004)
Generalist canid pathogens are of increasing concern to carnivore conservation. The continued encroachment of rapidly growing domestic dog (Canis familiaris) populations into wildlife areas provides increased opportunities for disease transmission between dogs and both terrestrial and aquatic wildlife species. The jackal species, widespread throughout sub-Saharan Africa and adaptable to both human-disturbed and protected landscapes, are thought to play a central role in the maintenance and transmission of generalist canid pathogens and to act as a source of infection for both wild and domestic species. This thesis investigates the role played by the black-backed jackal (Canis mesomelas) in the transmission and maintenance of canine distemper and other canid pathogens within a Namibian coastal carnivore guild, comprising black-backed jackals, brown hyenas (Hyaena brunnea), Cape fur seals (Arotocephalus pusillus pusillus), and domestic dogs from urban settlements. The first of the chapters containing original data, Chapter 3, describes a canine distemper outbreak in the jackals and dogs of the guild, providing the first evidence for, and a description of, natural canine distemper infection in jackals and demonstrates that this species was responsible for the rapid spread of the epidemic along the Namibian coast and for the spill-back of the virus into the dog population. Chapter 4 investigates the exposure of the sympatric Cape fur seal population to morbilliviruses using virus neutralisation -tests for canine distemper, phocine distemper and dolphin morbillivirus and demonstrates that it is unlikely that a morbillivirus is endemic in this population and that the seals did not suffer a large increase in seroprevalence or mortality as a result of the canine distemper outbreak in the jackals and dogs. In Chapter 5, serological data indicates that jackals and dogs both have high levels of exposure to canine adenovirus, canine herpesvirus and sarcoptic mange but that exposure to canine parvovirus, although high in the dogs is very low in the jackal population. Canine adenovirus and sarcoptic mange are likely to be endemic in the jackal and dog populations, hence jackals may act as a source of infection to sympatric wildlife and as a source of re-infection for dogs. In Chapter 6, behavioural observations of jackal-jackal and jackal-seal interactions are used to determine contact rates for the transmission of canine distemper virus. Contact rates of different subsets of the jackal population are compared to determine if there is any heterogeneity which would support the existence of a core group of individuals primarily responsible for the spread of canine distemper virus within the jackal population. Contact rates and overlap of jackal home ranges at the colony, as determined from radio-telemetry data are used to help understand the observed prevalence of exposure to canine distemper virus in the jackal and seal populations. The results of this study are discussed in relation to the control of distemper infection in wild and domestic canids, in Namibia and elsewhere in sub-Saharan Africa, and the importance of disease surveillance in jackal populations is stressed as disease management programs aimed at controlling canine distemper and other common viral infections in domestic dogs must assess the risk of re-infection from jackals or other sympatric wildlife species.
The importance of jackals and domestic dogs for the transmission of generalist canid pathogens to sympatric carnivores in Namibia